Is There A Need Instrument Volleyball Underhand Serve Using Artificial Intelligence? - Destriana, Destriana; Destriani, Destriani; Victorian, Ahmad Richad; Anggraini, Putri (STKIP PGRI Jombang, 2023)
Analyzing the need for the implementation of the development of the ball volleyball lower serve instrument is one of the right ways to design what instruments are in accordance with the wishes of students so that learning objectives can be achieved. The purpose of this study is to see whether there is a need for the development of an artificial intelligence technology ball volleyball lower serve instrument. This type of research is descriptive quantitative with survey as the method used. The test instrument used is a questionnaire distributed by google form. This research was conducted at SMA Negeri 1 Tanjung Batu with 194 respondents. The results of the study obtained students with a very needy category as many as 139 (71.65%), students with a needy category as many as 34 (17.53%) students, a moderate category of 7 (3.61%), a category of less need as many as 10 5.15%) and a category of very little need as many as 4 (2.06%) students. very low 24%. The findings of this study are that in general students at SMA Negeri 1 Tanjung batu need the development of an instrument for serving under volleyball with Artificial Intelligence technology, with these findings, it is used as a basis for conducting further research to develop products in the form of a test instrument for serving under volleyball with Artificial Intelligence technology.